Book Profile : Shopping malls and other sacred spaces: putting God in place - Rodkey, Christopher Demuth (The journal for cultural and religious theory, 2004)
A profile of "Shopping Malls and Other Sacred Spaces: Putting God in Place" by John Pahl. Grand Rapids, MI: Brazos, 2003. 288pp.